2012
DOI: 10.1111/j.1440-1681.2012.05715.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Lactam pharmacokinetics and pharmacodynamics in critically ill patients and strategies for dose optimization: A structured review

Abstract: SUMMARY1. Infections and related sepsis are two of the most prevalent issues in the care of critically ill patients, with mortality as high as 70%. Appropriate antibiotic selection, as well as adequate dosing, is important to improve the clinical outcome for these patients.2. b-Lactams are the most common antibiotic class used in critically ill sepsis patients because of their broad spectrum of activity and high tolerability. b-Lactams exhibit time-dependent antibacterial activity. Therefore, concentrations ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 106 publications
1
70
0
1
Order By: Relevance
“…It has been shown that the relevant pharmacokinetic/pharmacodynamic (PK/PD) parameter that predicts the activity of beta-lactams is the T ϾMIC (40). In a piglet tissue-cage model of the cephalosporin cefquinome, doses that achieved a T ϾMIC99 that was Յ25% of the dosage interval or a T ϾMPC that was Ն50% of the dosage interval were not associated with mutant enrichment in E. coli (22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the relevant pharmacokinetic/pharmacodynamic (PK/PD) parameter that predicts the activity of beta-lactams is the T ϾMIC (40). In a piglet tissue-cage model of the cephalosporin cefquinome, doses that achieved a T ϾMIC99 that was Յ25% of the dosage interval or a T ϾMPC that was Ն50% of the dosage interval were not associated with mutant enrichment in E. coli (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a paucity of pediatric literature related to the pharmacodynamics and kinetics of antibiotics in severe sepsis, there is a body of evidence in the adult literature showing that antibiotic levels of drugs such as ertapenem [58,59], beta-lactams and vancomycin may vary considerably in severe sepsis depending on the specific context [59][60][61][62][63], including albumin and creatinine levels. Drugs such as aminoglycosides may accumulate in patients with severe sepsis, but there may also be augmented excretion of antibiotics such as beta-lactams with resultant poor therapeutic levels [64].…”
Section: Antibioticsmentioning
confidence: 99%
“…The bactericidal and broad spectrum nature of β-lactams make them attractive in patients with sepsis. The time-over-MIC dependent killing with β-lactams would suggest benefit with administration as continuous infusion instead of intermittent dosing, particularly given the fluid shifts that occur in critically ill patients (5)(6)(7). Meta-analysis of studies comparing continuous infusions of β-lactams to standard intermittent dosing in acute infections have failed to find a consistent clinical benefit in mortality, infection recurrence, clinical cure, super-infection post-therapy, and safety outcomes in both critically-and non-critically ill patients (3,4,(8)(9)(10).…”
mentioning
confidence: 99%
“…For example, there is evidence that tissue levels of β-lactams in critically ill patients are lower than predicted from serum levels, and may be higher with continuous infusion (13)(14)(15). Given that β-lactams are hydrophilic, have a small distribution volume similar to extracellular water, and are predominantly excreted via the kidneys, one might expect a higher extracellular tissue level in critically ill patients who have capillary leak (resulting in expanded extracellular space) receiving continuous infusions (5,15 First, most patients in this study had lungs as infection source. In ventilator associated pneumonia (VAP) it is difficult to determine the organisms responsible for the infection, and it is possible that β-lactams were not optimal therapy for some.…”
mentioning
confidence: 99%
See 1 more Smart Citation